Blogi polityków. Kto, dlaczego i o czym pisze? - Bagieńska-Masiota, Aleksandra (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
Blogging is a global, widespread and fashionable phenomenon. While some European politicians blog, their American counterparts are in the lead in their pragmatic attitude to the Internet, approached as a means to win voters. Regardless of location, though, blogs spread ideas and present the candidate’s profile, whether by means of written or spoken (podcast) text. The first services facilitating blogs in Polish (e.g. Onet.pl) appeared in 2001–2002. At present blogs are written by representatives of the legislative and executive power, as well as by local authorities. Blogs play the role of political propaganda, featuring a combination of informative and persuasive functions. They are about presenting political issues in terms of conflict and struggle. Another significant function fulfilled by blogs is to raise a given politician’s profile. To a lesser extent, blogs also perform the function of personal space and provide information on the activities of the authorities.